Language Learning Beliefs of High School Students In Bangka Belitung - Husnayaini, Ihda (Scientia: Jurnal Hasil Penelitian, 2019)
Learning a foreign language is generally one of the most challenging subjects in high school. This study discussed the beliefs of foreign language learning of high school students in Bangka Belitung, Indonesia, who planned on learning Arabic and Japanese, especially the prevalence of beliefs among different classes of learners (Arabic, Japanese and mix class) and between female and male students. The result of this study suggested that there were differences of the responses to the inventory among classes and gender but they were not significant. The students responded five aspects concerning the beliefs and they had the highest scores in Motivations and Expectations, especially the mix language class. Furthermore, female students had more positive opinion about foreign language learning, which matched some previous studies revealing that female learners were better than males in language learning.